A Makerspace for Life Support Systems in Space. Issue 11 (November 2019) - Snyder, Jessica E.; Walsh, David; Carr, Peter A.; Rothschild, Lynn J.
Abstract : Human space exploration and settlement will require leaps forward in life support for environmental management and healthcare. Life support systems must efficiently use nonrenewable resources packed from Earth while increasingly relying on resources available locally in space. On-demand production of components and materials (e.g., 3D printing and synthetic biology) holds promise to satisfy the evolving set of supplies necessary to outfit human missions to space. We consider here life support systems for missions planned in the 2020s, and discuss how the maker and 'do-it-yourself' (DIY) biology communities can develop rapid, on-demand manufacturing techniques and platforms to address these needs. This Opinion invites the diverse maker community into building the next generation of flight hardware for near-term space exploration. Highlights: To establish a human settlement on the moon or Mars, NASA needs reliable life support systems that efficiently use nonrenewable resources packed from Earth while relying increasingly on resources available locally in space – solar energy and biological resources. Equipment for the life support system will need repair during multiyear missions. Earth will resupply when possible, but the crew will also make components in their own habitat during the mission. Both mechanical and biological ultra-low size, weight, and power (UL-SWaP) devices satisfy such technology gaps to continually maintain a habitable atmosphere. As pioneers of rapid prototyping on limited resources, the maker community could propel space travel forward by developing technologies consistent with the needs of human missions: efficient (UL-SWaP), automated, networked, and modular.